In Vitro Study on the Influence of Silver Diamine Fluoride on the Adhesion Strength of Dental Restorative Materials - Fernández-Mafé, Mónica; Armengol-Olivares, Andrea; Miralles-Jordá, Lucía; Vicente-Escuder, Ángel; Pérez-Bermejo, Marcelino; Narciso, Javier; Pallarés-Sabater, Antonio (Frontiers in Materials, 2022)
Silver diamine fluoride (SDF) has demonstrated its clinical success for years in the arrest of car-ies lesions, however, the influence it could have on the success of restorations after its application still remains unknown. The purpose of this research is to study the relationship between the use of SDF and adhesive strength of the materials used in restorations made with glass ionomer and composite resin, as well as with different adhesive systems. A sample consisting of 240 teeth di-vided into 8 groups with 30 teeth in each of them (n = 30) was used. In these groups, the use of res-toration with composite resin and glass ionomer was compared using different adhesive systems, with and without prior application of SDF. Notable differences in adherence were observed among the different groups depending on the filling material . There is also a significant effect of tooth type on adhesion. We can conclude that there is a relationship between the use of SDF and the adhesion between the tooth and the restorative materials analyzed.